Tsunami Hazard Evaluation for the Head of the Gulf of Elat–Aqaba, Northeastern Red Sea - Salamon, Amos; Frucht, Eran; Ward, Steven N.; Gal, Erez; Grigorovitch, Marina; Shem-Tov, Rachamim; Calvo, Ran; Ginat, Hanan (Frontiers in Earth Science, 2021)
Unique geological and seismotectonic settings may trigger a multi-cascading hazard and should be identified beforehand. Such is the head of the Gulf of Elat–Aqaba (HGEA) at the northeastern end of the Red Sea where its geology, tectonics, bathymetry, and earthquake and tsunami history exhibit clear potential for earthquake and submarine-landslide tsunami generation. We thus investigated the possible tsunamigenic sources in the gulf and evaluated the resulting hazard at the HGEA. First, we assembled a bathymetric grid and adopted GeoClaw software to simulate most of the earthquake-tsunami scenarios. Next, we resolved the scheme of the largest possible tsunamigenic earthquakes along the deep basins of the Gulf of Elat (GEA) and the associated Dead Sea rift valley, as well as the potential tsunamigenic submarine landslides in the HGEA. The use of GeoClaw was verified against the 1995 tsunami generated by the Nuweiba Mw 7.2 earthquake, and then operated to simulate a suite of earthquake scenarios. Results showed that the marginal faults of Elat Basin pose the highest tsunami hazard to the Israeli part of the HGEA. To better assess that hazard, we screened the geology and seismotectonics of the HGEA and found that the Elat normal fault presents the worst-case scenario for Elat city. It is capable of generating a multi-cascading threat of earthquake and submarine-landslide tsunami, local subsidence that can increase inundation, and above all, destructive ground motion. Scenarios of a tsunami caused by the worst-case earthquake on the Elat fault simulated by GeoClaw and Ward’s (2011) approach, and submarine landslide in the HGEA simulated by Wang et al.’s (2015) ‘Tsunami Squares’ approach, demonstrated waves as high as 4 m along these coasts. Accordingly, we constructed a map of the evacuation zone. We also show that strong ground-shaking and retreat of the sea at the HGEA should be considered a tsunami warning, although false alarms are inevitable. Furthermore, tsunami hazard exists all along the gulf and further assessments are needed to quantify this hazard and increase awareness among the area's population.